Bioactive Nutrient Fortified Fertilizer: A Novel Hybrid Approach for the Enrichment of Wheat Grains With Zinc - Ali, Muhammad Asif; Naeem, Farrukh; Tariq, Nadeem; Ahmed, Ijaz; Imran, Asma (Frontiers in Plant Science, 2021)
Zinc (Zn) is a critical micronutrient that synergizes nutrients use efficiency, improves plant growth and human health. Low Zn bioavailability in soils affects produce quality and agricultural productivity across the globe ultimately inducing deficiency in humans and animals. Zn deficiency is a leading cause of malnutrition in under-developed countries where a widespread population depends upon staple cereals for daily calories intake. Modern cereal cultivars are inherently low in Zn, eventually, plants need to be enriched with soil application of ZnSO4, but due to higher fixation losses, it becomes an inefficient source. Rhizosphere microbiome contains Zn-solubilizing bacteria (ZSB) that improve Zn-bioavailability thus increase the root function, Zn-uptake, and plant growth. Niha Corp developed a hybrid process of Bioactive Nutrient Fortified Fertilizer (BNFF) which has been used to formulate Zabardast Urea (ZU) by coating Bioactive Zn (BAZ) and ZSB on urea. Data obtained for 15 wheat varieties from 119 farmer field demonstration plots and eight replicated trials on 42 locations across multi-environment conditions concludes that ZU significantly improved the plant biomass and yield by 12% over no-Zn-control and produced grains with 57 μg/g Zn-contents which can meet a major part of the recommended dietary allowance (RDA) of humans. The study recommends that this microbe-mediated hybrid invention (ZU) is a feasible approach to boost Zn bioavailability, Zn-use efficiency, enhance yield and quality that may contribute to improve human health. To the best of our knowledge, this is the first wise-scale field testing of Zn-enrichment in grains of bread-wheat using an innovative BNFF Urea Z-technology.